2015
DOI: 10.1587/nolta.6.207
|View full text |Cite
|
Sign up to set email alerts
|

A novel cochlea partition model based on asynchronous bifurcation processor

Abstract: Abstract:The cochlea is a highly nonlinear biological sound processor the major components of which are lymph (viscous fluid), a basilar membrane (vibrating membrane in the viscous fluid), outer hair cells (active dumpers for the basilar membrane), inner hair cells (neural transducers), and spiral ganglion cells (parallel spikes density modulators). In this paper, a novel cochlea partition model based on a concept of an asynchronous bifurcation processor is presented. It is shown that the presented model can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…There have been various theoretical and circuit modeling studies on such nonlinear hearing characteristics, where their potential applications include cochlear implants . Among them, ergodic (or asynchronous) sequential logic (SL)-based cochlear models have been shown as much more hardware-efficient (e.g., consume fewer circuit elements and lower power) than ordinary differential equation (ODE)-based cochlear models [22][23][24][25][26][27][28][29][30]. In this paper, a novel hardware-efficient coupled ergodic SL-based cochlear model is presented.…”
Section: Introductionmentioning
confidence: 99%
“…There have been various theoretical and circuit modeling studies on such nonlinear hearing characteristics, where their potential applications include cochlear implants . Among them, ergodic (or asynchronous) sequential logic (SL)-based cochlear models have been shown as much more hardware-efficient (e.g., consume fewer circuit elements and lower power) than ordinary differential equation (ODE)-based cochlear models [22][23][24][25][26][27][28][29][30]. In this paper, a novel hardware-efficient coupled ergodic SL-based cochlear model is presented.…”
Section: Introductionmentioning
confidence: 99%
“…A number of electronic circuits cochlear models have been designed with strong emphases on their applications to cochlear implants [17][18][19][20][21][22][23][24][25][26]. In addition, it has been shown that ergodic sequential logic (SL) biomimetic models are much more hardware-efficient (e.g., consume fewer circuit elements and lower power) compared to standard ordinary differential equation (ODE) biomimetic models [25][26][27][28][29][30]. The results in this paper will be useful in developing a small and low-power cochlear implant that can reproduce the nonlinear sound processing functions of the human cochlea.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that the cochlea can be modeled as an array of such active oscillators slightly below the onset of spontaneous oscillation, which are coupled mechanically and through the lymphatic fluid with high viscosity in the cochlear duct [8][9][10][11][12][13][14]. Development of biomimetic acoustic sensors that take into account the amplification characteristics of the cochlea has also been attempted [3,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%